2018
DOI: 10.2471/blt.17.206466
|View full text |Cite
|
Sign up to set email alerts
|

Involving male partners in maternity care in Burkina Faso: a randomized controlled trial

Abstract: ObjectiveTo determine whether an intervention to involve the male partners of pregnant women in maternity care influenced care-seeking, healthy breastfeeding and contraceptive practices after childbirth in urban Burkina Faso.MethodsIn a non-blinded, multicentre, parallel-group, superiority trial, 1144 women were assigned by simple randomization to two study arms: 583 entered the intervention arm and 561 entered the control arm. All women were cohabiting with a male partner and had a low-risk pregnancy. Recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 35 publications
(37 reference statements)
0
75
0
Order By: Relevance
“…For instance, Yargawa and Leonardi-Bee in their systematic review and meta-analysis of men's involvement found that, men's involvement increases skilled birth attendance and use of postnatal care and also it was significantly associated with reduced odds of postpartum depression among women [22]. A randomized control trial among couples in Burkina Faso found that, couples who participated in the education-focused intervention were more likely to be exclusively breast-feeding three months postpartum and also use effective contraception eight months postpartum [23]. The study conducted in Southeast Nigeria found that men who were aware of female contraception had three times greater odds of having spouses who wanted to use contraception compared to men who were not aware of female contraception [24].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Yargawa and Leonardi-Bee in their systematic review and meta-analysis of men's involvement found that, men's involvement increases skilled birth attendance and use of postnatal care and also it was significantly associated with reduced odds of postpartum depression among women [22]. A randomized control trial among couples in Burkina Faso found that, couples who participated in the education-focused intervention were more likely to be exclusively breast-feeding three months postpartum and also use effective contraception eight months postpartum [23]. The study conducted in Southeast Nigeria found that men who were aware of female contraception had three times greater odds of having spouses who wanted to use contraception compared to men who were not aware of female contraception [24].…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that men play an important role in maternity health, they help in the respect of treatment [28]. However, challenges related to the health structure, the lack of privacy, is notable.…”
Section: Main Themes and Excerpts Main Challenges And Excerptsmentioning
confidence: 65%
“…This also helps address barriers such as financial constraints and fear that a disapproving husband might discover an implant insertion site. 28 Moreover, several studies have shown that providing men with information and involving them in counselling sessions can help them become more supportive of contraceptive use and more aware of the concept of shared decision-making. 28,29 Men's lack of access to information and services is a barrier to FP as they cannot share responsibility for FP if services and information do not reach them.…”
Section: Discussionmentioning
confidence: 99%
“…28 Moreover, several studies have shown that providing men with information and involving them in counselling sessions can help them become more supportive of contraceptive use and more aware of the concept of shared decision-making. 28,29 Men's lack of access to information and services is a barrier to FP as they cannot share responsibility for FP if services and information do not reach them. To encourage men's cooperation, it is important to start by understanding their views rather than relying on their partner's perception of them.…”
Section: Discussionmentioning
confidence: 99%